Marqibo® (vincristine sulfate liposome injection) improves the pharmacokinetics and pharmacodynamics of vincristine - Silverman, Jeffrey A.; Deitcher, Steven R. (Cancer chemotherapy and pharmacology, 2013)
Vincristine (VCR) is a mainstay of treatment of hematologic malignancies and solid tumors due to its well-defined mechanism of action, demonstrated anticancer activity and its ability to be combined with other agents. VCR is an M-phase cell cycle-specific anticancer drug with activity that is concentration and exposure duration dependent. The pharmacokinetic profile of standard VCR is described by a bi-exponential elimination pattern with a very fast initial distribution half-life followed by a longer elimination half-life. VCR also has a large volume of distribution, suggesting diffuse distribution and tissue binding. These properties may limit optimal drug exposure and delivery to target tissues as well as clinical utility as a single agent or as an effective component of multi-agent regimens. Vincristine sulfate liposome injection (VSLI), Marqibo ® , is a sphingomyelin and cholesterol-based nanoparticle formulation of VCR that was designed to overcome the dosing and pharmacokinetic limitations of standard VCR. VSLI was developed to increase the circulation time, optimize delivery to target tissues and facilitate dose intensification without increasing toxicity. In xenograft studies in mice, VSLI had a higher maximum tolerated dose, superior antitumor activity and delivered higher amounts of active drug to target tissues compared to standard VCR. VSLI recently received accelerated FDA approval for use in adults with advanced, relapsed and refractory Philadelphia chromosome-negative ALL and is in development for untreated adult ALL, pediatric ALL and untreated aggressive NHL. Here, we summarize the nonclinical data for VSLI that support its continued clinical development and recent approval for use in adult ALL.